Effect of Work Discipline on Employee Performance with Compensation as a Moderating Variable at PT Solusi Energy Nusantara - I Made Aryata; I Gede Marendra (Institute of Computer Science (IOCS), 2023)
PT Solusi Energy Nusantara (SENA) is a subsidiary of PT PGAS Solution which is engaged in the transmission and distribution of natural gas where the company has been trusted by several large companies in Indonesia. However, employee performance has decreased by 7% in 2021 when compared to 2019, this will certainly affect the company's performance in facing future business competition. There are several factors that influence employee performance, one of which is compensation and work discipline. From the results of research conducted using the SEM AMOS method, it can be concluded that compensation has an effect on employee performance with a p-value of 0.001 while work discipline has no effect on employee performance with a p-value of 0.698. However, when compensation as a moderating variable will strengthen the relationship between work discipline and employee performance so that work discipline affects employee performance with a p-value of 0.002.